The Effectiveness of Alternative Marketing Strategies and Trust in Improving Purchase Decisions of Fashion Products on E-Commerce Platform - Rizky Aldiansyah; Dimas Ditio; May Dedu; Agustina (Mabsya: Jurnal Manajemen Bisnis Syariah, 2025)
In the market, people exchange goods and services with one another to satisfy their wants, including those related to fashion. The global fashion industry has changed due to the advances in information and communication technologies, especially in consumer purchasing patterns. Especially in consumer purchasing patterns, the convenience offered by e-commerce platforms is the main reason why many people now prefer to buy all their needs, including fashion products. This study aims to identify “the effectiveness of alternative marketing strategies and trust in improving purchase decisions of fashion products on e-commerce platforms”. This research used the quantitative method with a linear regression technique, using 277 respondents from the TikTok shop users as the object of the research. The findings indicate that the parameters examined in this study positively influence a person's decision to purchase a product on an online marketplace. In this study, alternative promotion strategies, namely online customer reviews, content marketing, and flash sales, were also found to be some promotional ideas that can be used to increase sales. Additionally, trust is a factor that influences a person's decision to buy a product favorably by giving them a stimulus that increases their confidence in their choice.